Adaptive encoding scheme providing optimal performance for Internet of Things industry in the backscatter system - Jae-Hyun Ro; Bit-Na Kwon; Seongjoo Lee; Hyoung-Kyu Song (International Journal of Distributed Sensor Networks)
In the wireless communication market, Internet of Things is one of the major issues. Internet of Things is a technology which connects all objects to the Internet and enables to share the information of the objects with each other. Also, energy harvesting for batteryless devices is also one of the new issues in order to realize Internet of Things. Through the realization of Internet of Things, all objects can connect to the Internet and share own information with each other. Since the sensor communication with the low-power battery or without the battery is possible by the backscatter technique, a backscatter technique is highly useful for the realization of Internet of Things. This article proposes a scheme that a sensor is connected to the Internet and the optimal performance is obtained. For reliable backscatter technique for mobile user, this article proposes the two encoding schemes which are FM0 and Miller- n . Also, to minimize the loss of the data rate, these two encoding schemes are adaptively used according to mobility. The mobility is decided by signal-to-noise ratio and channel state. For mobile user, the proposed backscatter technique has high error performance due to proposed adaptive encoding scheme.